BENTUK BIMBINGAN PENGGELOLAAN PERSYARATAN KESEHATAN AIR BAGI PELAKU USAHA KOLAM RENANG - Nopianti, Nia -; Barhamudin, Barhamudin; Hendra, Hendra; Roni, Abdul (Faculty of Law, University of Palembang, 2024)
Every time you carry out swimming pool business management activities, you always have provisions for guidance in carrying out activities that require clean and hygienic water for health. This research uses an empirical normative system which starts from the requirement that the applicable provisions listed apply to real events among many audiences. The results of this research can be summarized that according to Ministry of Health Regulation No. 32 of 2017, the guidance methods that are mandatory for business managers in realizing clean water and hygiene for health are internal control methods. Internal control is guidance carried out by or for business managers who are supposed to prepare water for the general public or trade. not only carried out based on their needs and does not fulfill their overall obligations as stated in the health minister's regulations. That this regulation provides legal sanctions against business actors who do not meet the Health Standards for clean and hygienic pool water. The forms of supervision carried out by swimming pool business actors must be carried out optimally in accordance with the regulations that have been implemented so that activities run well and smoothly for business actors and consumers who use swimming pool services.